Influence of Growth Need Strength on the Relationship between Overall Life Satisfaction and Job Satisfaction for Medical Service Quality and Delivery - Nizam Sarkawi; Abdul Rahman Jaafar; Jauriyah Shamsuddin; Noor Fareen Abdul Rahim; Efrizal Syofyan (International Journal of Supply Chain Management, 2019)
This study is to determine the influence of Growth Need Strength [GNS] between overall life satisfaction and job satisfaction among SRN’s. Data were collected through survey using questionnaire. This study employed stratified random sampling involving a total of 390 nurses at selected general hospitals. The finding of the study contributes in the specific area of literature, theory and also in research design. The results of this study suggest that the GNS as moderator have played significant important role between overall life satisfaction and job satisfaction. It is also to improve medical service quality and delivery in order to provide a much better conducive working environment by incorporating policies that can improve job satisfaction.